2019
DOI: 10.1021/acs.chemrestox.9b00286
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modifications of Globular Proteins Phototriggered by an Endogenous Photosensitizer

Abstract: The main goal of the present work was to investigate the damages photoinduced by pterin (Ptr), an endogenous photosensitizer present in human skin under pathological conditions, on a globular protein such as ubiquitin (Ub). A particular attention has been paid on the formation of covalent adducts between Ptr and the protein that can behave as photoantigen and provoke an immune system response. Here, a multifaceted approach including UV/visible spectrophotometry, fluorescence spectroscopy, electrophoresis, size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…28 Several studies have demonstrated that pterin (Ptr), the parent and unsubstituted compound of oxidized pterins (Figure 1B), can photosensitize proteins, such as albumin 29,30 and ubiquitin. 31 The studies performed using human serum albumin (HSA) revealed that the photosensitizer induces chemical changes in the protein in, at least, two amino acids: W and tyrosine (Y), 30 the latter being responsible of the oligomerization of the protein through the formation of tyrosine dimers (Y 2 ). The photooxidation of W and Y does not significantly affect the secondary and tertiary structures of HSA.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…28 Several studies have demonstrated that pterin (Ptr), the parent and unsubstituted compound of oxidized pterins (Figure 1B), can photosensitize proteins, such as albumin 29,30 and ubiquitin. 31 The studies performed using human serum albumin (HSA) revealed that the photosensitizer induces chemical changes in the protein in, at least, two amino acids: W and tyrosine (Y), 30 the latter being responsible of the oligomerization of the protein through the formation of tyrosine dimers (Y 2 ). The photooxidation of W and Y does not significantly affect the secondary and tertiary structures of HSA.…”
supporting
confidence: 92%
“…It is known that, under UV-A irradiation, Ptr can produce the oxidation of W and Y residues, and it also induces the dimerization of the latter. 30,31,42 HlyA contains four W residues and forty Y residues in its sequence, 5 so it is expected that HlyA will be affected by the photosensitization process. On the contrary, alkyl groups, because they are saturated, 43 will not be oxidized by photosensitization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ptr-photoinduced one-electron oxidation of Tyr moiety leads to dimerization of free Tyr (36) and cross-linking of peptides (40,41) and proteins (42,43) (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%